Association Between Aspartate Aminotransferase to Alanine Aminotransferase Ratio and Incidence of Type 2 Diabetes Mellitus in the Japanese Population: A Secondary Analysis of a Retrospective Cohort Study - Chen L (Dove Medical Press, 2021)
Lidan Chen,1,* Kebao Zhang,2,* Xue Li,2 Yang Wu,3 Qingwen Liu,4 Liting Xu,1 Liuyan Li,4 Haofei Hu5 1Shenzhen Nanshan Medical Group Headquarter, Shenzhen, Guangdong Province, 518000, People’s Republic of China; 2Department of Emergency, The Eighth Affiliated Hospital, Sun Yat-sen University, Shenzhen, 518000, Guangdong Province, People’s Republic of China; 3Department of Endocrinology, Shenzhen Second People’s Hospital, Shenzhen, 518000, Guangdong Province, People’s Republic of China; 4Shenzhen Second People’s Hospital, Shenzhen, 518000, Guangdong Province, People’s Republic of China; 5Department of Nephrology, Shenzhen Second People’s Hospital, Shenzhen, 518000, Guangdong Province, People’s Republic of China*These authors contributed equally to this workCorrespondence: Haofei HuDepartment of Nephrology, Shenzhen Second People’s Hospital, No. 3002 Sungang Road, Futian District, Shenzhen, 518000, Guangdong Province, People’s Republic of ChinaTel +86-755-83366388Email huhaofei0319@126.comBackground: The study on the association between aspartate aminotransferase to alanine aminotransferase (AST/ALT) ratio and the risk of type 2 diabetes mellitus (T2DM) was limited. Therefore, we conducted a secondary analysis based on online data to explore whether there was an association between the AST/ALT ratio and incident T2DM among a large number of Japanese people.Methods: The study was a retrospective cohort study. We downloaded the NAGALA (NAfld in Gifu area) data from DATADRYAD website between 2004 and 2015. This present study included 15,291 participants. Cox proportional-hazards regression, generalized additive models and subgroup analyses were used to find out the association between the AST/ALT ratio and T2DM events.Results: The negative relationship was shown between AST/ALT ratio and incident T2DM (HR = 0.617, 95% CI: 0.405– 0.938) in our study. A non-linear relationship and saturation effect were found between them, and the inflection point was 0.882. It indicated that the AST/ALT ratio was negatively correlated with incident T2DM when the AST/ALT ratio was less than the inflection point (HR = 0.287, 95% CI: 0.126– 0.655, p = 0.0030). We found that exercise modified their relationship (P for interaction = 0.0024), and people who did not exercise associated strongly (HR = 0.464 95% CI: 0.290– 0.741).Conclusion: AST/ALT ratio was negatively associated with T2DM risk, and their relationship was non-linear and had a saturation effect. When the AST/ALT ratio was less than 0.882, they showed a significant negative correlation.Keywords: alanine aminotransferase, aspartate aminotransferase, type 2 diabetes mellitus, nonlinearity